2017
DOI: 10.1596/1813-9450-8096
|View full text |Cite
|
Sign up to set email alerts
|

Rural Non-Farm Employment and Household Welfare: Evidence from Malawi

Abstract: The Policy Research Working Paper Series disseminates the findings of work in progress to encourage the exchange of ideas about development issues. An objective of the series is to get the findings out quickly, even if the presentations are less than fully polished. The papers carry the names of the authors and should be cited accordingly. The findings, interpretations, and conclusions expressed in this paper are entirely those of the authors. They do not necessarily represent the views of the International Ba… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
11
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 22 publications
(54 reference statements)
0
11
0
Order By: Relevance
“…The need for panel data largely explains why dynamic aspects are understudied, as many studies on rural wage Ó 2020 The Agricultural Economics Society employment use cross-sectional data. Moreover, studies that do use longitudinal data typically only estimate effects of entry into non-farm employment (Bezu et al, 2012;Adjognon et al, 2017a).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…The need for panel data largely explains why dynamic aspects are understudied, as many studies on rural wage Ó 2020 The Agricultural Economics Society employment use cross-sectional data. Moreover, studies that do use longitudinal data typically only estimate effects of entry into non-farm employment (Bezu et al, 2012;Adjognon et al, 2017a).…”
Section: Introductionmentioning
confidence: 99%
“…An older literature points to economy-wide linkages from the farm to the non-farm sector, emerging from production and consumption linkages and resulting in growth multiplier effects (Haggblade et al, 1989;Delgado et al, 1998). More recent studies investigate investment and knowledge spillover effects from the rural non-farm economy on agricultural production at the household level (Ruben and van den Berg, 2001; Kilic et al, 2009;Oseni and Winters, 2009;Stampini and Davis, 2009;Anrıquez and Daidone, 2010;Mathenge et al, 2015;Smale et al, 2016;Amare and Shiferaw, 2017;Adjognon et al, 2017a). In the latter strand of literature as wellwith the exception of the Mathenge et al (2015) and Smale et al (2016) studiesdifferent types of wage and self-employment are pooled, making it impossible to detect linkages between agricultural and non-agricultural wage employment on the one hand and self-employment on the other, and disentangle different channels of effects.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…ROFEAs provides vital income diversification and access to cash at key moments especially in West Africa, where the risks of farming are high and rural savings, credit and insurance mechanisms are poorly developed or not available (Adewunmi et al 2013). Rural off-farm economic activities may among other things; absorb surplus labour in rural areas, help farm-based households spread risks, offer more remunerative activities to supplement or replace agricultural income, offer income potential during the agricultural offseason, and provide a means to cope or survive when farming fails (Loughrey et al2017;Bezu and Holden, 2014;Davis et al, 2017;Adjognon et al 2017). In terms of employment, Sheahan and Christopher (2014) believe that the share of the off-farm sector in rural employment in developing countries varies from 20% to 50%.…”
mentioning
confidence: 99%
“…In terms of employment, Sheahan and Christopher (2014) believe that the share of the off-farm sector in rural employment in developing countries varies from 20% to 50%. In terms of income, Davis et al, 2017 andAdjognon et al 2017 found rural non-farm income shares in Africa to be ranging from 22% to 93% and Egyei and Adzoror (2013) agreed that 30-50% is common in sub-Saharan Africa. Haggblade et al (2010) indicate that off-farm income accounts for between 35% and 50% of total income of rural households in developing countries.…”
mentioning
confidence: 99%